Answer: -2 Step-by-step explanation: 2x-y=-8-1equation 2x=-8+y x=-8+y -2equation 2 then, taking 1st equation; 2x-y=-8 2(-8+y/2)-y=-8 -16+2y-y=-8 4 -16+2y–4y=-8 4 -16-2y=-8*4 -2y=-32+16 y=-16/-2 y=4 for x x=-8+y 2 x=-8+4 2 x=–4 2 x=-2 Log in to Reply

the answer for this question is x-2

Answer:-2

Step-by-step explanation:2x-y=-8-1equation

2x=-8+y

x=

-8+y -2equation2

then, taking 1st equation;

2x-y=-8

2(-8+y/2)-y=-8

-16+2y-y=-84

-16+2y–4y=-84

-16-2y=-8*4

-2y=-32+16

y=-16/-2

y=4

for x

x=

-8+y2

x=

-8+42

x=

–42

x=-2